Pertumbuhan Perekonomian Pulau Jawa Tahun 2014-2019 - Laras Maodi (2021)
This study discusses the determinants of economic growth determined by local taxes, regional levies, foreign direct investment (PMA) and domestic investment (PMDN). The results show that regional taxes and regional levies have proven to have an effect on economic growth because regional taxes are one of the determining factors that play a major role in economic growth, as well as regional levies which are also one of the determinants of economic growth. Furthermore, FDI and domestic investments have been proven to have no effect on economic growth due to FDI and domestic investment in Indonesia, poor infrastructure and logistics conditions and the lack of strong legal certainty.